Some Comments on London Theory for Superconductors - M. A. Grado Caffaro; M. Grado Caffaro (Active and Passive Electronic Components)
The basic formulae of London theory for superconductors are reviewed. Moreover, an expression for the spatial charge density in a type-II superconductor is obtained; this equation is associated with sinusoidal oscillations. Considerations on both penetration depth and coherence length are exposed.